Effect of a magnetic field in an S=1 antiferromagnetic chain with single-ion anisotropy and alternating bonds with disorder - Salmon, Octavio D. R.; Neto, Minos A.; Branco, Nilton S.; Cotta, E. A.; Fonseca Filho, H. D.; Silva, Jonathas N. [UNESP] (Elsevier B.V., 2021)
this study, we investigated the quantization of magnetization at low temperatures in a spin-1 antiferromagnetic chain with single-ion anisotropy by considering the quenched disorder in alternating bonds. Each spin i interacts with its nearest neighbors via J(i) and alpha J(i) couplings, where J(i) is considered to obey a Gaussian or Bernoulli probability distribution function, with width sigma. Zero temperature phase diagrams were obtained by minimizing the energy of the Hamiltonian. For finite temperatures, a transfer matrix technique was applied in order to treat the partition function. Consequently, the magnetization curve calculated by deriving the quenched average of the free energy exhibited interesting plateaus, which were modified when randomness was considered. Experimentally, these plateaus appear when some chain structures are subjected to a magnetic field.
Keywords: Low-dimensional system; Super-lattice chain; Single-ion anisotropy; Magnetization plateau